Kurikulum Sejarah Jenjang SMA: Sebuah Perbandingan Indonesia-Australia - Abrar Abrar (Jurnal Pendidikan Sejarah, 2015)
The purpose of this paper was to compare how the education system and curriculum history at secondaryschool level between Indonesia and Australia. The education system in Indonesia is not much differentfrom Australia. History curriculum in Indonesia philosophically is more multi dimensional thanAustralia which essentialism as priority. Indonesian history curriculum is more comprehensive intermsof content than Australia that is optional for students. The ability to interpret the history curriculum inAustraliais more prominent than Indonesia.